MATHEMATICS TEACHERS’ AND TUTORS’ IMPRESSION ON THE CONCEPT AND STRUCTURE OF THE OPTIMISING PROBLEM SOLVING (OPS) FRAMEWORK - Shinta Sari (Euclid, 2023)
A number of frameworks have been proposed to help students become more adept at solving mathematical problems, including Problem Based Learning (PBL), Research Skill Development (RSD), Blooms' Taxonomy, and Optimising Problem Solving (OPS). One of the most recent frameworks created by professionals in issue solving is the Optimising issue Solving (OPS) framework. It has been demonstrated to enhance students' ability to solve engineering-related problems. Consequently, the OPS framework might potentially be a different framework for mathematics teachers and tutors. This research aims to analyse teachers’ and tutors’ impression on the concept and structure of the OPS framework. The study are categorised into an ethnographic by using a thematic content analysis approach. It resulted in two concepts and two structures of the OPS framework that impress the mathematics teachers and tutors. The concepts are related to the non-sequential facets and the facet titles. While, the structure of the framework that impress the teachers and tutors are related to the pentagon shape, and the word and colour format. Keywords. Framework, Optimising Problem Solving, Mathematics Learning